Hey Alexa … examine the variables influencing the use of artificial intelligent in-home voice assistants - McLean, Graeme; Osei-Frimpong, Kofi (Computers in human behavior, 2019)
Artificial Intelligent (AI) In-home Voice Assistants have seen unprecedented growth. However, we have little understanding on the factors motivating individuals to use such devices. Given the unique characteristics of the technology, in the main hands free, controlled by voice, and the presentation of a voice user interface, the current technology adoption models are not comprehensive enough to explain the adoption of this new technology. Focusing on voice interactions, this research combines the theoretical foundations of U&GT with technology theories to gain a clearer understanding on the motivations for adopting and using in-home voice assistants. This research presents a conceptual model on the use of voice controlled technology and an empirical validation of the model through the use of Structural Equation Modelling with a sample of 724 in-home voice assistant users. The findings illustrate that individuals are motivated by the (1) utilitarian benefits, (2) symbolic benefits and (3) social benefits provided by voice assistants, the results found that hedonic benefits only motivate the use of in-home voice assistants in smaller households. Additionally, the research establishes a moderating role of perceived privacy risks in dampening and negatively influencing the use of in-home voice assistants. •Use of AI in-home voice assistants is driven by utilitarian & symbolic benefits.•Social benefits (attractiveness & presence) motivate VA use.•Hedonic benefits have no influence on motivating VA use.•Perceived privacy risks has a dampening and negative effect on VA use.•Household size influences the benefits motivating VA use.